Describing proof on hybrid model of ICT and collaborative learning - Nadar, Nityashree; Iyer, Dr.R.Kamatchi (International Journal of Engineering and Technology, 2018)
This paper analysis document to explore tendencies of implementing of ICT in social media and collaborative learning which was explained in the previous paper with an experiment using the study of algebra data set. After analysing the hybrid model, this paper explains the analysis of that novel approach has another remarkable role as a developer and source of innovation. A proposed model that has been suggested to form a starting point for the next ICT education.